Ableism, Accessibility, and Educational Development: A Disability Studies Perspective. (12th June 2019) - Trybus, Matthew J.; Breneman, Daisy L.; Gravett, Emily O.
Abstract: This chapter analyzes educational development through the lens of disability studies, exposing commonplace barriers and providing recommendations to ensure those who identify as having a disability are included in programming.